The Food and Agricultural Organization of the United Nations’ (FAO) Intervention to the Covid-19 impacts on food security in Nigeria, 2019-2021 - Nneka Sophie Amalu; Emeka Melvin Amalu; Yisrael Ini-obong Jack-Rabin; Melvina Amalu (Universitas Negeri Makassar, 2022)
Food insecurity has remained a problem in Nigeria despite its abundance in agricultural resources. However, the situation exacerbated with the outbreak of the COVID-19, as prices of foods increased and food shortages were experienced due to restrictions placed by the government to contain the virus. Thus, as persons battled to control the spread of the virus, they also battled with hunger, malnutrition and starvation. Covid-19 pandemic impacted food security by reducing purchasing power of individual and households due to job loss; reduced the availability and affordability of food due to the restrictions on movement, interstate travels and border closures; food transportation and distribution were also disrupted amongst other factors. Due to these negative impacts, interventions to manage the widespread food insecurity had to be launched by individuals, private companies, religious bodies, government and international organisations in order to alleviate the food crises induced by Covid-19. The thrust of this paper is to examine the Food and Agricultural Organisations’ intervention to the COVID-19 impacts on Food security in Nigeria. The paper proffers viable ways for more international engagement in order to solve the problem of food insecurity in Nigeria.